Reflection on racialization, whiteness, and researcher positionality as 'not-quite-white' in the field of educational studies - Basha, Shpresa (Reconceptualizing Educational Research Methodology, 2025)
This article draws on two autoethnographic vignettes from an ethnographic field study conducted in a Danish elementary school over six months. By unfolding two vignettes from photo-elicitation interviews (PEIs), the study analyses how researcher positionality relates to students’ experiences of marginalization and makes feelings of being racialized or othered come to the fore. The study proposes the notion of ‘sticky’ emotion and affect as an analytical lens that provides a more critically reflexive analytical framework to address the interactions between the researcher, racialized students, positionalities, and the research process. The purpose of this paper is to contribute to the discussion and reflection on racialization and whiteness to challenge the pull of racialization. The theoretical framework draws on the concepts of whiteness and racialization, which is followed by methodological reflections on researcher positionality. Keywords: researcher positionality, vignette, affect, ‘sticky’ emotion, racialization, whiteness, Nordic exceptionalism, ethnography, racialized students